Imunização de bezerros contra anaplasmose com amostra atenuada de Anaplasma marginale - José Carlos Vilas Novas (1978)
In order to check the efficiency of an attenuated A. marginale vaccine 17 holstein friesian calves aging from 11 to 90 days, were inoculated with 2m1 intramusculary, on 2 farms in the Minas Gerais State (Farm A Pedro Leopoldo and Farm B Betim). On farm A, 7 calves were vaccinated and 6 were kept as controls ando n Farm B, 10 were vaccinated and 8 were kept as controls. On both farms these calves were left on concret under constant observation in order to avoid ticks parasitism and after 5 weeks they were exposured on the Field. Card test, PCV, blood smears stainned by Giemsa and clinical observations were made before vaccination and after that every 15 days. The retal temperature was taken dayly during 70 and 50 days respectively, to farms A and B. In aproximatelly 4 weeks after vaccine inoculation 57% of the calves on farm A showed slight parasitemia (0.2 1.0%) by A. marginale and the majority (71.43%) showed increase of temperature over 40°C on days 23 to 25 after vaccination. After exposured on the field the calves (vaccinated and controls) suffered slight decrease on their PCV. After 15 days of the vaccine innoculation on the calves of the farm B, slight PCV drop was noted, but no parasited erytrocyte was found on this occasion. Seventy por cent of these calves showed increase of temperature over 40°C on days 13 to 28. The parasitemia of the vaccinated calves were almost all the time inferior to that showed by controls. The vaccine gave 100% of protection vaccinated calves, and 57% of the controls showed clinical signs of the disease. The diseased calves were treated with 500mg of tetracycline by 3 consecutives days, recovering from clinical signs, except one Who died.